Parametric and sensitivity analysis of a PCM-integrated wall for optimal thermal load modulation in lightweight buildings. (25th March 2021) - Kishore, Ravi Anant; Bianchi, Marcus V.A.; Booten, Chuck; Vidal, Judith; Jackson, Roderick
Highlights: Parametric and sensitivity analysis on PCM-integrated lightweight building walls. Combinatory effects of various PCM parameters on thermal load modulation are examined. Optimal PCM with optimal precooling completely inverts transient heat gain profile of the wall. Up to 70% reduction of wall-related heat gain during peak hours can be achieved. Abstract: Load modulation in buildings is becoming increasingly important due to growing disparity in energy demand during peak and off-peak hours. Integrating phase change material (PCM) in building envelopes and using a controlled precooling strategy can provide substantial thermal load modulation; however, it may greatly increase the total energy use. Previous studies have employed PCM in building envelopes primarily for energy savings and, to some extent, peak load shedding and shifting. However, the load modulation capacity of a PCM-integrated envelope has not been well explored in the literature. In this study, we perform an extensive parametric and sensitivity analysis on PCM-integrated lightweight building walls and examine the combinatory effects of various PCM parameters on thermal load modulation and wall-related heat gains in buildings. Using numerical simulations, we investigate eight PCM parameters: PCM location in the wall, transition temperature, thickness, latent heat, transition range, density, specific heat, and thermal conductivity. We evaluate their impact and relative importance to achieve maximum load modulation in buildings without compromising occupants' thermal comfort or total energy use. The results show that the optimized PCM proposed in this study can completely invert the transient heat gain profile of the wall, providing up to 70% reduction of wall-related heat gain during peak hours without a major increase in the cumulative heat gain.